Overcoming EGFRG724S-mediated osimertinib resistance through unique binding characteristics of second-generation EGFR inhibitors. Issue 1 (December 2018) - Fassunke, Jana; Müller, Fabienne; Keul, Marina; Michels, Sebastian; Dammert, Marcel; Schmitt, Anna; Plenker, Dennis; Lategahn, Jonas; Heydt, Carina; Brägelmann, Johannes; Tumbrink, Hannah; Alber, Yannic; et al.
Abstract The emergence of acquired resistance against targeted drugs remains a major clinical challenge in lung adenocarcinoma patients. In a subgroup of these patients we identified an association between selection ofEGFR T790M -negative butEGFR G724S -positive subclones and osimertinib resistance. We demonstrate thatEGFR G724S limits the activity of third-generation EGFR inhibitors both in vitro and in vivo. Structural analyses and computational modeling indicate thatEGFR G724S mutations may induce a conformation of the glycine-rich loop, which is incompatible with the binding of third-generation TKIs. Systematic inhibitor screening and in-depth kinetic profiling validate these findings and show that second-generation EGFR inhibitors retain kinase affinity and overcomeEGFR G724S -mediated resistance. In the case of afatinib this profile translates into a robust reduction of colony formation and tumor growth ofEGFR G724S -driven cells. Our data provide a mechanistic basis for the osimertinib-induced selection ofEGFR G724S -mutant clones and a rationale to treat these patients with clinically approved second-generation EGFR inhibitors. Acquired resistance to targeted drugs remains a major clinical challenge in lung adenocarcinoma patients. Here, the authors show how the acquiredEGFR G724S mutation induces resistance to third-generation EGFR inhibitors and why the mutant kinase remains susceptible to second-generation inhibitors.